Women's Reproductive Rights (Comparative Family Planning in Indonesia, Malaysia, and Turkiye) in Islamic Perspective - Mammenasa Daeng Yusuf, Siti Sahnia; Akbarizan; Munir, Akmal Abdul; Fahlevi, M Reza (Universitas Medan Area, 2025)
This article aims to determine women's reproductive rights (comparative family planning in Indonesia, Malaysia, and Turkey) in an Islamic perspective. The problem is focused on women's reproductive rights using family planning. Data were collected by reviewing related research, as well as the Qur'an and laws and regulations using a literature approach method analyzed qualitatively. This study concludes that women's reproductive rights in Indonesia, Malaysia, and Turkey in the Family Planning (KB) program are equally important, although women are still the main users of family planning, their reproductive rights are still burdened. Women must be good mentally, physically, and socially, especially in reproductive rights with the importance of male participation, and freedom to determine their physical and mental choices, and the need to overcome factors that violate women's reproductive rights. The use of family planning in Indonesia, Malaysia, and Turkey differs from the focus of the objectives, the main methods used, and the meaning of the function of family planning from each country. The form of comparison of women's reproductive rights in the Family Planning (KB) program in Indonesia, Malaysia, and Turkey still prioritizes Islamic teachings in KB, which is permitted as long as it is in accordance with Islamic teachings with the aim of regulating spacing and not limiting children except for certain reasons such as threatening the reproductive health of women or men for the common welfare and the impact on state goals.